Bioprocess for Production, Characteristics, and Biotechnological Applications of Fungal Phytases - Jatuwong, Kritsana; Suwannarach, Nakarin; Kumla, Jaturong; Penkhrue, Watsana; Kakumyan, Pattana; Lumyong, Saisamorn (Frontiers in Microbiology, 2020)
Phytases are a group of enzymes that hydrolyze the phospho-monoester bonds of phytates. Phytates are one of the major forms of phosphorus found in plant tissues. Fungi are mainly used for phytase production. The production of fungal phytases has been achieved under three different fermentation methods including solid-state, semi-solid-state and submerged fermentation. Agricultural residues and other waste materials have been used as substrates for the evaluation of enzyme production in the fermentation process. Nutrients, physical conditions such as pH and temperature, and protease resistance are important factors for increasing phytase production. Fungal phytases are considered monomeric proteins and generally possess a molecular weight of between 14–353 kDa. Fungal phytases display a broad substrate specificity with optimal pH and temperature ranges between 1.3–8.0 and 37–67 C, respectively. The crystal structure of phytase has been studied in Aspergillus. Notably, thermostability engineering has been used to improve relevant enzyme properties. Furthermore, fungal phytases are widely used in food and animal feed additives to improve the efficiency of phosphorus intake and reduce the amount of phosphorus in the environment.